2016
DOI: 10.1111/mpp.12486
|View full text |Cite
|
Sign up to set email alerts
|

Maize susceptibility to Ustilago maydis is influenced by genetic and chemical perturbation of carbohydrate allocation

Abstract: The ability of biotrophic fungi to metabolically adapt to the host environment is a critical factor in fungal diseases of crop plants. In this study, we analysed the transcriptome of maize tumours induced by Ustilago maydis to identify key features underlying metabolic shifts during disease. Among other metabolic changes, this analysis highlighted modifications during infection in the transcriptional regulation of carbohydrate allocation and starch metabolism. We confirmed the relevance of these changes by est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 79 publications
4
41
0
1
Order By: Relevance
“…Nevertheless, this result is consistent with previous studies that described an increase in starch content of chloroplasts inside infected areas (Snetselaar & Mims, ). However, several previous studies on starch content in U. maydis ‐infected tissue reported diverse results (Doehlemann et al ., ; Horst et al ., ; Kretschmer et al ., 2016b). Besides an influence of different sampling conditions and varying types of tissue, this also indicates that the U. maydis ‐induced starch accumulation is a very local effect, which is restricted to the tumorous tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, this result is consistent with previous studies that described an increase in starch content of chloroplasts inside infected areas (Snetselaar & Mims, ). However, several previous studies on starch content in U. maydis ‐infected tissue reported diverse results (Doehlemann et al ., ; Horst et al ., ; Kretschmer et al ., 2016b). Besides an influence of different sampling conditions and varying types of tissue, this also indicates that the U. maydis ‐induced starch accumulation is a very local effect, which is restricted to the tumorous tissue.…”
Section: Resultsmentioning
confidence: 99%
“…() revealed that functions for photosynthesis, such as CO 2 fixation, chlorophyll biosynthesis or photosystem‐related proteins of the chloroplast, were down‐regulated during tumour formation (Table , see Fig. S1 and Text S1, Supporting Information; Kretschmer et al ., ). The observed negative impact on the expression of chloroplast functions is interesting because of the chlorosis and chlorophyll changes that occur in tumours at later stages of disease, as is macroscopically evident from their white appearance (Horst et al ., ; Fig.…”
Section: Resultsmentioning
confidence: 97%
“…This approach allows the scoring of increased and decreased symptoms of the infected plants. The infections were scored after 14 days, as described previously (Kretschmer et al ., ). For why1‐2 , the number of plants available for the study was somewhat limited.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations